Interregional and Regional Input-Output Analysis: A Model of a Space-Economy - Isard, Walter (The Review of Economics and Statistics, 1951)
FOR more than four decades the construction of a general location theory has been a stimulating challenge to spatial theorists. Despite the productive efforts of Weber, Englander, Predohl, Ohlin, Palander, Hoover, Losch, and others, the goals of spinning a theoretical web and specifying the design of a corresponding operational model are still remote.2 However, the comparatively recent pioneering contributions of Leontief in developing input-output techniques for general equilibrium analysis are of consequence here. They permit an attack upon a specific set of significant problems which logically fall within the jurisdiction of a general theory of location and space-economy. analysis of changing interregional economic bonds and flows can be approached from several directions. input-output method as elaborated here implicitly assumes, for the most part, unchanging spatial relations between any producer and his suppliers. Only a limited amount of industrial relocation can be tolerated with any change in the basic parameters of the economic system at any given point of time. An alternative approach has been sketched for example in an unpublished memorandum by Koopmans.3 Such an approach would treat the space factor explicitly. It would permit major variation in the spatial extent of production for each firm and in the pattern of production and resource utilization. It would be consistent with major relocation of industry and population. It would reveal how distance actively conditions interregional economic relations.4 An operational model following this alternative, more desirable, approach is yet to be developed. This paper is concerned with the much more limited assignment of regional and interregional analysis within the rigid spatial framework necessitated by the postulates of input-output analysis.5 'The analysis in this article has greatly benefited from discussions with Guy Freutel and with Wassily W. Leontief, James S. Duesenberry, Leon Moses, and other members of the Harvard Economic Research project. However, the shortcomings of the analysis and the views expressed herein are the author's only. model to be developed through spatial aggregation is basically different from one constructed by Professor Leontief through national disaggregation (in his forthcoming Studies in the Structure of the American Economy, Chapter 4). Nevertheless, the two models should not be viewed as alternatives. Rather they are complements. Leontief balanced regional model is particularly useful for determining regional implications of national projections; the pure interregional model, for determining national implications of regional projections. (For elaboration of this point, see W. Isard and G. Freutel, Regional and National Product Projections and Their Interrelations, sections 7 and 8, paper prepared for Conference on Research in Income and Wealth, National Bureau of Economic Research, May 195I,) Since one can proceed by degrees from one type of model to the other, it is likely that after considerable experimentation an hybrid model, involving elements of both, may prove to have the most general utility. author's experience in directing the preparation and collection of the data and in carrying through the computations for the Leontief model has been of great value in setting up a feasible design for his own model. 'For a presentation and evaluation of these efforts see W. Isard, The General Theory of Location and SpaceEconomy, Quarterly Journal of Economics, Vol. 63 (November I949), pp. 476-506. 3T. Koopmans, Optimum Geographical Distribution of Population and Industry in the United States (Cowles Commission for Research in Economics, January I946). 'Though trade theory is basically concerned with flows, it has by and large ignored or set aside the space factor. This is in line with the economic theorist's customary preoccupation with the time factor. ;;Treating space implicitly or as a passive factor has also been characteristic of the better regional development studies. Colin Clark in his excellent works on economic progress in the various regions and nations of the world (The Conditions of Economic Progress, London, I940, and Economics of I960, London, I942) does not attempt at all to study the basic changes in the spatial interrelations and patterns of these nations or regions. Nor does he probe into the diverse spatial structures of nations and regions at a given point of time. To be sure, he makes spatial comparisons in the sense that he compares nations having different latitudinal and longitudinal positions. But such comparisons more accurately fall under the heading of description, not spatial analysis. A. J. Brown (Industrialization and Trade, London, I943, and Applied Economics, London, I947), in ascribing a significant role to the world's uneven pattern of resources and its implications for specialization and the global locational structure of industry, takes a major step forw7ard. But he does not transcend geographic positional analysis. He does not expose the fundamental spatial scaffolding of international relations. Nor do E. F. Staley (Woorld Economic Development, Montreal, I944), the